BIMA PORT AND THE BIMA SULTANATE IN ARCHAEOLOGICAL STUDIES - Izzal Faturrahmi Audina; Nayati, Widya (Satmata: Journal of Historical Education Studies, 2024)
The archipelago's ancient spice trade involved many regions and one of them was Bima during the period from Kerajaan Bima to Kesultanan Bima. Bima has a port which is hidden from the southern route via Laut Flores, so to reach it the traders have to go along Bima Bay. This research raises issues related to the background of the placement Bima port and Bima Sultanate complex and also Bima port’s characteristics. This archaeological research uses archaeological, landscape and historical data that collected through surveys, observations and literature studies to be analyzed using data analysis, landscape analysis and comparative analysis. The results of this research are that the placement of the Bima port and the Bima Sultanate complex is based on the history of Bima and the location is safe. The location of the Bima port is suitable as a place to unload anchor, shelter from pirates and the wind, and also to refill supplies for traders. Bima Port is classified as a small port because its commodities are not the main commodities for archipelago trade and the number and variety of arrivals is small. The conclusion is Bima port played a major role in the development of the Bima Kingdom and Sultanate as a place of trade and access that connected Bima with other regions or kingdoms. The port plays as dealer for commercial commodities from the region and its surroundings to be brought to larger cities or ports.